Pengaruh imbuhan tepung daun kelor (Moringa oleifera Lam.) dalam pakan pada kandungan protein dan kolesterol telur itik pengging (Anas platyrhyncos domesticus L.) - Khunfaya Firnanda Putri Rossida; Sunarno Sunarno; Kasiyati Kasiyati; Muhammad Anwar Djaelani (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
One important component contained in Moringa leaves is protein. Apart from protein, bioactive flavonoids and saponins in Moringa leaves have potential as antioxidants and hypocholesterolemia. The objective of this study was to analyze the effect of Moringa leaf flour as a feed additive to protein content and cholesterol of Pengging duck eggs. The study design used was a Completely Randomized Design (CRD) with 5 treatments, and each treatment consists of 3 replications. The treatment group consisted of a control group and a basal feed treatment that was added with Moringa leaf flour by 2.5; 5; 7.5; and 10%. Measurement of duck egg protein content using the Bradford method and cholesterol measured by the Indiko method. Data were analyzed with one-way ANOVA. The addition of Moringa leaf flour on feed did not have a significant effect (P > 0.05) on the protein content and cholesterol of the Pengging duck eggs. The percentage of white and egg yolk weights did not increase significantly. The conclusion of this study was the use of Moringa leaf flour as a feed additive with a concentration of 2.5 to10% could not change the protein content and cholesterol of the Pengging duck eggs.